CT-guided percutaneous spine biopsy in suspected infection or malignancy: a study of 214 patients = CT-gesteuerte perkutane Wirbelsäulenpunktionen bei Verdacht auf Infektion oder Tumor : eine Studie mit 214 Patienten - Rehm, Johannes; Akbar, Michael; Kauczor, Hans-Ulrich; Weber, Marc-André (RöFo, 2016)
Purpose: To retrospectively determine the effectiveness and accuracy of CT-guided percutaneous biopsy of malignant and inflammatory bone lesions of the spine and to assess the reliability of pre-biopsy CT and MRI. Materials and Methods: 214 patients with lesions of the spine, which were suspicious either for being malignant or inflammatory, underwent CT-guided biopsy for pathological and/or microbiological detection. Biopsy samples were sent for histological examination in 128/214 patients, for microbiological analysis in 17/214 patients and for both analyses in 69/214 patients. Retrospectively, the diagnostic accuracy and sensitivity/specificity of the pre-interventional imaging (CT and MRI) were determined. In addition, the influence of the biopsy on subsequent patient management was assessed. Results: The accuracy was 94.4 % for histopathological analysis and 97.7 % for microbiological analysis. In 25 % of cases the microbiological analysis revealed an underlying pathogen that was not significantly affected by pre-biopsy antibiotic therapy. The sensitivity/specificity of the pre-biopsy cross-sectional imaging concerning suspected malignancy was 69 %/78 %. For suspected infection, the sensitivity/specificity of pre-biopsy imaging was 81 %/44 %. In 52 % of all cases, the biopsy result changed subsequent patient management. Conclusion: Percutaneous CT-guided spine biopsy is a useful and reliable diagnostic procedure to establish a definitive diagnosis but with a relatively low yield of microorganisms in the case of infection. Key Points: • CT-guided spine biopsy is an accurate and reliable procedure in case of infection and tumour. • The results of the CT-guided spine biopsy have a significant influence on the subsequent patient management. • Pathogen recovery-rate in case of infection is moderate but not significantly affected by prebiopsy antibiotic therapy. Citation Format: • Rehm J, Veith S, Akbar M et al. CT-Guided Percutaneous Spine Biopsy in Suspected Infection or Malignancy: A Study of 214 Patients. Fortschr Röntgenstr 2016; 188: 1156 - 1162